Studi Dampak Penerapan Teknologi Artificial Intelligence terhadap Pemahaman Mahasiswa Jurusan Pendidikan Teknik Elektro di Universitas Negeri Medan - S, Syaifullah; Gunawan, Adhinda Chyntia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study is to evaluate how much impact the use of AI has on the understanding of students of the Electrical Engineering Education Department, State University of Medan. This study uses a qualitative descriptive approach with data collection techniques through the distribution of Google forms. Questions are given to respondents, which can be used to determine their answers. In this study, 20 respondents were students of the Electrical Engineering Education Department. This study found that the understanding of students of the Electrical Engineering Education Department is greatly influenced by AI technology.